Dynamic Dissection of the Endocytosis of Porcine Epidemic Diarrhea Coronavirus Cooperatively Mediated by Clathrin and Caveolae as Visualized by Single-Virus Tracking - Yangyang Li (American Society for Microbiology, 2021)
Emerging and re-emerging coronaviruses cause serious human and animal epidemics worldwide. For many enveloped viruses, including coronavirus, it is evident that breaking the plasma membrane barrier is a pivotal and complex process, which contains multiple dynamic steps.